Penetration of Enrofloxacin in Aqueous Humour of Avian Eyes - Katrin Fuchs; Monika Rinder; Richard Dietrich; Leena Banspach; Hermann Ammer; Rüdiger Korbel (Veterinary Sciences, 2022)
Enrofloxacin has been shown to be appropriate to treat bacterial eye infections in mammals. However, the anatomy and physiology of the avian eye substantially differ from those in mammals, and pharmacokinetic data substantiating the clinical efficacy of enrofloxacin in birds are still lacking. In total, 40 chickens (Gallus gallus, Lohman Selected Leghorn) received single intramuscular administration of enrofloxacin at a dosage of 25 mg/kg body weight (BW). Serial blood and aqueous humour samples were taken at 12 different time points after administration (0–60 min and 2–32 h) and were analysed for their fluoroquinolone concentrations using a competitive enzyme immunoassay. The metabolization of enrofloxacin to ciprofloxacin was determined using liquid chromatography-mass spectrometry. The maximum serum concentrations of fluoroquinolones were observed at the time point of 2.82 ± 0.1 h and amounted to 10.67 ± 0.5 µg/mL. Fluoroquinolones redistributed to a minor extent into the aqueous humour reaching maximum concentrations of 4.52 ± 1.2 µg/mL after 7.54 ± 1.0 h of drug administration. The mean residence time (MRT), volume of distribution (Vd), and terminal half-life (t1/2 ß) were 1.68-, 2.84-, and 2.01-fold higher in aqueous humour than in serum, indicating that fluoroquinolones were trapped in aqueous humour. Enrofloxacin was only marginally metabolized into ciprofloxacin. A single intramuscular injection of a therapeutical dose of enrofloxacin (25 mg/kg BW) thus generated sustained and therapeutically active levels of enrofloxacin in the aqueous humour of chicken eyes.